(untitled) (Sciences & Technologie. C, Biotechnologies, 2011)
The results concerning the selection index applied to grasshoppers-preys of common kestrel show that Pamphagus elephaswith 12.37 present the most elevated value, follow-up by Pezotettix giornaïwith 2.85. For birds preys the count of this index shows that its value is high for the hybrid Sparrow Passer domesticusx P. hispaniolensisin 1998 (1.93), in 1999 (1.79) and in 2000 (2.12) as well as for Streptopelia senegalensisin 2000 (1.92).